2019
DOI: 10.1016/j.jhep.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Global liver disease burdens and research trends: Analysis from a Chinese perspective

Abstract: Liver diseases affect millions of people worldwide. In most developed countries, the incidence of viral hepatitis is waning as a result of modern advances in disease prevention, diagnosis, and therapies. Expanded programmes for systematic immunisation against hepatitis B virus have also significantly brought down the number of new cases in many countries, including China. In contrast, with the improvement in living standards, the prevalence of metabolic liver diseases including non-alcoholic fatty liver diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
277
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(280 citation statements)
references
References 37 publications
2
277
1
Order By: Relevance
“…Chronic alcohol-related liver injury and viral hepatitis are two major categories of chronic liver disease, and often both etiologies occur in the same liver, accelerating liver disease progression [34]. The prevalence rates of hepatitis C virus (HCV) infection in the US, European countries and Japan were reported to be 1.13%, 1.10%, and 1.56%, respectively, and these rates are higher than that of 0.72% in China [35]. A national household survey conducted between 1999-2002 in the United States showed that adults who were HCV RNA-positive had heavier alcohol intake, were almost three times more likely to consume >1 drink per day (35.3% vs. 13.5%, P=0.003), and were almost 8 times more likely to consume >3 drinks per day (19.2% vs. 2.4%, P=0.010) compared with other adults [36].…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%
“…Chronic alcohol-related liver injury and viral hepatitis are two major categories of chronic liver disease, and often both etiologies occur in the same liver, accelerating liver disease progression [34]. The prevalence rates of hepatitis C virus (HCV) infection in the US, European countries and Japan were reported to be 1.13%, 1.10%, and 1.56%, respectively, and these rates are higher than that of 0.72% in China [35]. A national household survey conducted between 1999-2002 in the United States showed that adults who were HCV RNA-positive had heavier alcohol intake, were almost three times more likely to consume >1 drink per day (35.3% vs. 13.5%, P=0.003), and were almost 8 times more likely to consume >3 drinks per day (19.2% vs. 2.4%, P=0.010) compared with other adults [36].…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%
“…e global prevalence of NAFLD is currently estimated to be 14-32% [6]. And, in China, the incidence of NAFLD is reckoned to be approximately 20.0% [8], which is rapidly increasing due to the more frequent occurrence of metabolic syndrome [9]. Currently, NAFLD has become the main cause of abnormal liver biochemical indicators in health checkups in China, which is the major issue of chronic liver disease worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Liver failure is considered as the inability of the liver to perform its normal synthetic and metabolic function as part of normal physiology [1]. According data from 11 representative hospitals in China, about 5% of liver diseases patients suffered liver failure [2]. Liver failure may occur acutely without any underlying liver disease (acute liver failure, ALF), as an acute decompensation of chronic liver disease ('acute-on-chronic' liver failure, ACLF) or as a chronic decompensation of end-stage liver disease.…”
Section: Introductionmentioning
confidence: 99%